2017
DOI: 10.1161/strokeaha.117.018270
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Good Outcome After Endovascular Therapy for Vertebrobasilar Occlusion Stroke

Abstract: In our retrospective case series, only smoking, low baseline National Institutes of Health Stroke Scale score, and successful reperfusion status were associated with good outcome in patients with posterior circulation stroke treated with endovascular therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
97
7
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(119 citation statements)
references
References 26 publications
14
97
7
1
Order By: Relevance
“…Age, stroke severity at admission, and time from symptom onset to groin puncture did not differ between PCS and ACS in their study. Similar to a retrospective case series of 214 patients with PCS from two US academic institutions, a lower NIHSS score at admission and successful recanalization were associated with favourable outcome in our study .…”
Section: Discussionsupporting
confidence: 86%
“…Age, stroke severity at admission, and time from symptom onset to groin puncture did not differ between PCS and ACS in their study. Similar to a retrospective case series of 214 patients with PCS from two US academic institutions, a lower NIHSS score at admission and successful recanalization were associated with favourable outcome in our study .…”
Section: Discussionsupporting
confidence: 86%
“…The previously identified factors independently associated with a good outcome after endovascular therapy in posterior circulation stroke included a low baseline NIHSS, successful reperfusion, a history of smoking, a high DWI‐Acute Stroke Program Early CT Score (ASPECTS), a shorter time to the start of procedure, a shorter time to reperfusion, better collateral status, and magnetic resonance imaging–based patient selection 3, 7, 9, 18, 19. Recently, Gory et al reported that only the failure to achieve successful reperfusion was an independent predictor of mortality at 3 months, in patients with acute BAO who underwent thrombectomy 20.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recent acceptance of thrombectomy as the standard of care in patients with acute anterior circulation stroke,4 the effectiveness and safety of modern thrombectomy remains uncertain for patients with acute BAO. Although multiple case studies have described endovascular therapy for acute BAO, previous studies are limited by small sample sizes, heterogeneous patient populations, and the use of older generation devices and techniques 3, 5, 6, 7, 8, 9. Moreover, several important issues remain to be elucidated, such as identifying predictors of functional outcome after modern thrombectomy or the selection of a first‐line thrombectomy technique for patients with acute BAO.…”
Section: Introductionmentioning
confidence: 99%
“…GFR was analyzed as a continuous variable to evaluate the association with outcomes in uni-and multivariate logistic regression analyses and additionally dichotomized into < 60 or ≥60 mL/min/1.73 m 2 . Thrombolysis in cerebral infarction scores were dichotomized into 0-2a and 2b-3 [18]. The difference of GFRs at baseline and at discharge was calculated in each patient, and the one sample t test was used to test for significant changes.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison of our results to former reports is therefore confined. One study that evaluated predictors of good outcome after endovascular therapy for vertebrobasilar stroke observed that higher creatinine levels at admission were associated with poor outcome in univariate analysis [18]. However, this association was no longer present in multivariate testing, and associations between impaired renal function and ICH were not described [18].…”
Section: Discussionmentioning
confidence: 99%